Strategizing New Growth Methods to City Shophouses - Ee, Siaw Jia; Hamat, Wan Mazlan Wan (MAJ - Malaysia Architectural Journal, 2023)
Evidence of city shophouses can be found in abundance in Kuala Lumpur for the past few decades (Gullick, 2000). Besides the rapid urbanization of Kuala Lumpur, land scarcity has become a major issue in the city where every piece of lands is considered valuable properties for development. However, due to the nature and limitations of city shophouses, they do not reduce the scarcity issue resulting in majority of shophouses to be demolish just for complete redevelopment (Wagner, 2017). Therefore, ideation needs to be done for city shophouses which represents typology of a past era. The research methods used for this research will be qualitative interviews on factors leading to its decline and the prevalent strategies to revitalize it. The research will ideate the future possibility of city shophouses in term of its history, place-making, and necessities for the community in attempt to contribute in improving shophouse typology across all places and serve as a design framework in the future. Variables such as materiality and engineering can be further researched to formulate the ideal method of implementing the research.